Effects of micro jets on the flow field of the duct with sudden expansion - Akhtar, Mohammad Nishat; Abu Bakar, Elmi; Aabid, Abdul; Khan, Sher Afghan (Blue Eyes Intelligence Engineering & Sciences, 2019)
This paper presents the results of an experimental investigation to study the effectiveness of the control jets to control base pressure in rapidly expanded circular tubes. Four tiny jets of 1 mm orifice diameter located at ninety degrees interval in cross shape along a pitch circle diameter of 1.3. The Mach number, the L/D ratio, and the area ratio of the study were 2.8, from 1 to 10, and 4.84, respectively. The nature of the flow field, the development of the flow in the duct, as well as the static wall pressure distribution in the duct was measured and discussed. The results indicate that the tiny jets can be used as an active dynamic controller for the base pressure. The wall pressure distribution is not adversely influenced by the small jets. From the present investigation, it is evident that for a given Mach number and nozzle pressure ratio one can identify the minimum duct L/D needed for the flow remained attached with the wall of the duct. The trend for the duct length L = 5D seems to show different results, due to the influence of back pressure and the peak pressure values are also less than that those were for higher L/D ratios, especially in respect of L/D = 5. Further, the flow field has smoothened in the duct, and wall pressure values with and without micro jets are identical. This trend continues until L/D = 4, then later for lower L/Ds like L/D = 3, the flow seems to be attached at higher NPRs. But for lower NPRs the flow is not attached.